Copper deposition in oligodendroglial cells in an autopsied case of hepatolenticular degeneration. Issue 3 (21st February 2018) - Nishimuta, Mayu; Masui, Kenta; Yamamoto, Tomoko; Ikarashi, Yuichi; Tokushige, Katsutoshi; Hashimoto, Etsuko; Nagashima, Yoji; Shibata, Noriyuki
Abstract : We present a case of hepatolenticular degeneration, so‐called Wilson's disease (WD), in a 31‐year‐old Japanese man with broader deposition of copper in the liver, kidney and brain. The liver showed severe cirrhotic changes with macronodular pseudolobule formation, but there was little difference in immunohistochemical expression patterns of the copper transporter ATP7B between the control and present case. In the brain, there were both WD‐related lesions such as the scattering of Opalski cells and changes caused by hepatic encephalopathy including the appearance of Alzheimer type II glia. Of note, we identified copper deposits in the systemic organs, including hepatocytes, renal tubules, and in broad areas of the brain. Surprisingly, as a result of further pursuit, copper accumulation in the brain was rarely identified in neuronal cells, but in Olig2‐positive glial cells with double immunohistochemical staining. Together, this rare autopsied case suggests a novel cellular candidate affected by abnormal copper metabolism and the necessity to perform the systemic examination of copper deposition in WD.